Exosome microsphere/nano silver loaded injectable antibacterial hydrogel augments anti-infection and healing for scald wound - Li, Rongkai; Qi, Qinbing; Jiang, Xiaojing; Gao, Zhongfei; Xie, Xianrui; Zhao, Yuqing; Cheng, Xiaochen; Wang, Chunhua; Hou, Guige; Li, Chengbo (Frontiers in Microbiology, 2025)
Infectious scald is recognized as a life-threatening concern in clinical due to easy infection and hard recovery. Exosomes possess cell migration, proliferation and angiogenesis under the containing rich growths factors, which may be a possibility for the treatment of scald chronic wounds. However, the instability and release issues of exosomes limits the storage and therapeutic efficacy. Herein, in this study, exosomes were successfully encapsulated calcium alginate microspheres, effectively avoiding the leakage and inactivation of exosomes. Meanwhile, composite hydrogel (HS-QAF-AgNPs) was fabricated with and quaternized carboxymethyl chitosan (Q-CMC), aldehyde group-modified alginate (ASA) with assisted crosslinking of ferric ion and dopped nano silver (AgNPs). The incorporation of exo-CAMs into the hydrogel protects the exosomes from harsh environmental conditions and extends their diffusion time, thereby guaranteeing a better therapeutic effect. Q-CMC and AgNPs altogether endow the hydrogel system with an inherent antibacterial effect against pathogenic microorganisms. In vitro and in vivo investigations demonstrated that the HS-QAF-AgNPs hydrogel was cytocompatibility, possessed antibacterial and hemostatic properties, promoted cell migration and cell proliferation, stimulated angiogenesis, regulated inflammatory response, delayed apoptosis, enhanced collagen deposition and accelerated wound closure. Thus, the multifunctional HS-QAF-AgNPs hydrogel dressing is expected to be a promising candidate for the treatment of severe scalds. There is an urgent need to develop multifunctional wound dressings that can coordinate cell migration, proliferation, apoptosis, collagen formation and remodeling, alongside inflammation and angiogenesis to promote skin wound closure.